1995
DOI: 10.1128/jvi.69.9.5320-5331.1995
|View full text |Cite
|
Sign up to set email alerts
|

Nucleotide sequence and protein analysis of a complex piscine retrovirus, walleye dermal sarcoma virus

Abstract: Walleye dermal sarcoma virus (WDSV) is a fish retrovirus associated with the development of tumors in walleyes. We have determined the complete nucleotide sequence of a DNA clone of WDSV, the N-terminal amino acid sequences of the major proteins, and the start site for transcription. The long terminal repeat is 590 bp in length, with the U3 region containing consensus sequences likely to be involved in viral gene expression. A predicted histidyl-tRNA binding site is located 3 nucleotides distal to the 3 end of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
52
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(55 citation statements)
references
References 45 publications
3
52
0
Order By: Relevance
“…Retrovirus particles have been observed by Walker (1961) and later by Yamamoto et al (1985b) in walleye tumors. Walleye dermal sarcoma virus (WDSV) genome has been cloned directly from tumors and sequenced, showing that it is a complex retrovirus (Martineau et al 1991(Martineau et al , 1992Holzschu et al 1995). Virions of WDSV have been observed by electron microscopy, and the genome has been detected by in situ hybridization in tumors at high levels when collected in the spring (Poulet et al 1995).…”
Section: Walleye Dermal Sarcomamentioning
confidence: 99%
See 1 more Smart Citation
“…Retrovirus particles have been observed by Walker (1961) and later by Yamamoto et al (1985b) in walleye tumors. Walleye dermal sarcoma virus (WDSV) genome has been cloned directly from tumors and sequenced, showing that it is a complex retrovirus (Martineau et al 1991(Martineau et al , 1992Holzschu et al 1995). Virions of WDSV have been observed by electron microscopy, and the genome has been detected by in situ hybridization in tumors at high levels when collected in the spring (Poulet et al 1995).…”
Section: Walleye Dermal Sarcomamentioning
confidence: 99%
“…Above 20ЊC, the viral enzyme activity dropped. It is also possible that the replication cycle of the virus may be restricted at higher temperatures, leading to the seasonal changes that are observed (Holzschu et al 1995).…”
Section: Viral Factorsmentioning
confidence: 99%
“…Examples of herpesviral-induced neoplastic conditions include salmonid herpesvirus II and cyprinid herpesvirus I, both of which cause mortalities in young fish and papillomas in some older survivors (Kimura & Yoshimizu 1989;Sano et al 1991). The genus Epsilonretrovirus contains the complex retroviruses that infect fish (Edien et al 2010;Goff 2013), several of which have been partially or completely sequenced (Bowser & Casey 1993;Holzschu et al 1995;Basta et al 2009;Coffee et al 2013). The pathology of retroviralassociated tumours in fish has been reviewed by Coffee et al 2013.…”
mentioning
confidence: 99%
“…Experimental transmission demonstrated that development of tumors on walleyes is greatest at water temperatures of 15ЊC, intermediate at 20ЊC, and least at 10ЊC (Bowser et al 1990). The causative virus is a member of the family Retroviridae, and the 12.7-kb genome has been completely sequenced (Holzschu et al 1995). Walleye discrete epidermal hyperplasia is a lesion found on walleyes that appears grossly as white areas on the body of the fish.…”
mentioning
confidence: 99%